Rapid Population Decline of the Pillar Coral Dendrogyra cylindrus Along the Florida Reef Tract - Neely, Karen L.; Lewis, Cynthia L.; Lunz, Kathleen S.; Kabay, Lystina (Frontiers in Marine Science, 2021)
Coral reefs worldwide are in a state of decline, but the population status and impacts of stressors for rare species are generally not well documented using broad-scale monitoring protocols. We fate-tracked all known colonies of the pillar coral, Dendrogyra cylindrus, on the Florida Reef Tract (FRT) from 2013 to 2020 to assess population condition and trend, and to document the relative impacts of chronic and acute stressors. Large average colony size, an absence of juveniles, and large geographic distances between genotypes suggest that the Florida D. cylindrus population has been reproductively extinct for decades. During the study period, low-intensity chronic stressors were balanced by regrowth, while back-to-back years of coral bleaching and thermally-exacerbated disease led to declines that the subsequent recovery rates suggest would require 11 uninterrupted years to overcome. The most recent stressor on Florida’s D. cylindrus population is “stony coral tissue loss disease” (SCTLD). Following the appearance of the disease in Florida in 2014, unrecoverable losses occurred within the D. cylindrus population as tissue, colonies, and whole genotypes suffered complete mortality. Losses of 94% of coral tissue, 93% of colonies, and 86% of genotypes between 2014 and the end of 2020 have led to functional extinction of D. cylindrus on the FRT.